An American-Vietnamese Cross-cultural Study of Interrupting and Asking for Clarification in Business Meetings : M.A Thesis Linguistics: 60 22 02 01 - Bùi, Thị Mai (ĐHNN, 2017)
This paper is carried out at endeavor of exploring the linguistic politeness strategies utilized by the Vietnamese and the American businesspeople in making interruption and asking for clarification in business meetings. From that, major similarities and differences between the two languages in this regard are revealed. On the basis of quantitative method, discourse completion task (DCT) is employed to collect data from participants including thirty Vietnamese native speakers and American ones who are currently working in business sector. The result reveals that the positive politeness strategy namely “minimizing imposition” is the most common strategy used by American businesspeople while their Vietnamese counterparts prefer “apologizing and minimizing imposition” in semiformal and informal business meetings. Moreover, the speaker’s ages, genders and positions have great influence on the choice of politeness strategy for Vietnamese businesspeople while those factors make no significant influence on the American ones.